Glucitol Dehydrogenase from Peach (Prunus persica) Fruits is Regulated by Thioredoxin h - Hartman, Matias Daniel (2014)
Glucitol (Gol) is a major photosynthetic product in plants from the Rosaceae family. Herein we report the molecular cloning, heterologous expression, and characterization of Gol dehydrogenase (GolDHase, EC 1.1.1.14) from peach (Prunus persica) fruits. The recombinant enzyme showed kinetic parameters similar to those reported for orthologous enzymes purified from apple and pear fruits. The activity of recombinant GolDHase was strongly inhibited by Cu2+ and Hg2+, suggesting that it might have cysteine residues critical for functionality. Oxidizing compounds (like diamide, hydrogen peroxide, and oxidized glutathione) inactivated the enzyme, whereas its activity was restored after incubation with reduced glutathione and thioredoxin from Escherichia coli. Recombinant thioredoxin h from peach fruits also recovered the activity of oxidized GolDHase. Our results suggest that peach fruit GolDHase could be redox regulated in vivo and this would be of relevance to determine carbon assimilation and partitioning in plants accumulating sugar alcohols.